دور الإرضاع المبكر في سير الطور الثالث للمخاض - عبد الرحمن, أحمد; الدالي, عصام; إسماعيل, ميسون (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي باللاذقية في الفترة بين كانون الأول 2002-حزيران 2003, وشملت الدراسة 200 ماخض خروس قسمت إلى أربع مجموعات: المجموعة الأولى: تضم 50 ماخضاً لم ترضع مباشرة بعد الولادة. المجموعة الثانية: تضم 50 ماخضاً أرضعت لمدة خمس دقائق. المجموعة الثالثة: تضم 50 ماخضاً أرضعت لمدة عشر دقائق. المجموعة الرابعة: تضم 50 ماخضاً أرضعت لمدة خمس عشرة دقيقة. - إحصائياً تبين لنا أن الإرضاع الطبيعي المبكر يسرع انفكاك المشيمة ويقلل كمية النزف. - بناءً على النتائج السابقة نوصي بالإرضاع الطبيعي المبكر بعد الولادة. This study was contucted at Al-Assad Univercity Hospital in Lattacia during the period from January 2002-June 2003 and included 200 nulliparous. Parturients were divided into four groups: The first group included 50 partureints who didn’t nurse after delivery. The second group included 50 partureints who nursed for 5 minutes. The third group included 50 partureints who nursed for 10 minutes. The fourth group included 50 partureints who nursed for 15 minutes. Statistically we found out that early Breast- Feeding accelerates the separation of placenta and reduces the amount of hemorrhage. Based on the results we advocate Breast- feeding immediately after delivery.